Developing the Composting Technology of Oil Palm Empty Fruit Bunch (OPEFB) Using Fast Ligninocellulolytic Degrading Fungi - Cassandra Sully, Jamau (Universiti Malaysia Sarawak, UNIMAS, 2010)
A study of optimization of time of incubation and volume of inoculums of the composting process was carried out to determine the best time of incubation and best inoculum volume of Cerrena unicolor inoculum in order to enhance the OPEFB composting process. Glucose analysis using DNS solution was performed to investigate the best time of incubation and the best volume of Cerrena unicolor. A lab scale composting was conducted on compost piles without fungal inoculation and inoculated compost. Several analyses were done in order to measure important parameters, such as pH, temperature and moisture content, in composting. Insoluble lignin analysis was conducted to measure the ability of Cerrena unicolor to degrade lignocelluloses materials. Phytotixicity test was carried out in order to measure the percentage of phytotoxic materials found in both compost piles. Alkaline pH was observed in both compost piles. No considerable differences of temperature were found in both compost piles. Inoculated compost piles obtained optimum moisture around 50-70 % while control compost moisture content was a bit low. Inoculated compost showed lower lignin content than control compost. Both compost piles showed germination index of higher than 80 %, indicating the phytotoxic materials had been eliminated. Further evaluation on temperature and phytotoxicity test should be done to confirm the elimination of pathogens and phytotoxic compounds.